Combined Administration of Human Ghrelin and Human Growth Hormone Attenuates Organ Injury and Improves Survival in Aged Septic Rats - Weng-Lang Yang; Gaifeng Ma; Mian Zhou; Monowar Aziz; Hao-Ting Yen; Spyros A Marvropoulos; Kaie Ojamaa; Ping Wang (BMC, 2016)
Abstract Sepsis is a major healthcare concern, especially in the elderly population. The use of an animal model closely resembling clinical conditions in this population may provide a better prediction in translating bench studies to the bedside. Ghrelin inhibits sympathetic nerve activity and inflammation in young septic animals; however, aged animals become hyporesponsive to ghrelin. In this study, we evaluated the efficacy of combined human ghrelin and growth hormone (GH) for sepsis treatment in the elderly utilizing a clinically relevant animal model of sepsis. Male Fischer 344 rats 22 to 24 months old were subjected to cecal ligation and puncture (CLP). Human ghrelin plus GH or vehicle (normal saline) was administered subcutaneously at 5 h after CLP. At 20 h after CLP, blood and tissue samples were collected for various analyses. Combined treatment attenuated serum levels of lactate, lactate dehydrogenase, creatinine, blood urea nitrogen, interleukin-6 (IL-6) and tumor necrosis factor-α (TNF-α) in aged septic rats. The integrity of the microscopic structure in the lungs, liver and kidneys was well preserved after treatment. Expression of IL-6, TNF-α, macrophage inflammatory protein-2 and keratinocyte-derived chemokine as well as myeloperoxidase activity and caspase-3 activation were significantly reduced in the lungs and liver of treated rats. Moreover, treated rats showed an improvement in cardiovascular function and increased expression of ghrelin receptor and c-fos in the brainstem. Finally, the 10-d survival of aged septic rats was increased from 29% to 64% after combined treatment and was associated with less body weight loss. Our findings warrant the development of combined human ghrelin and GH for sepsis treatment in the geriatric population.